Glaucomatous and Age-Related Changes in Corneal Pulsation Shape. The Ocular Dicrotism - Danielewska, Monika E.; Krzyżanowska-Berkowska, Patrycja; Iskander, D. Robert (PloS one, 2014)
To ascertain whether the incidence of ocular dicrotic pulse (ODP) increases with age, it is more pronounced in glaucomatous than in normal eyes and whether it is related to cardiovascular activity. 261 subjects aged 47 to 78 years were included in the study and classified into four groups: primary open angle glaucoma (POAG), primary angle-closure glaucoma (PACG), glaucoma suspects with glaucomatous optic disc appearance (GODA) and the controls (CG). Additionally, in each group, subjects with ODP were divided into two age subgroups around the median age. A non-contact ultrasonic method was used to measure corneal indentation pulse (CIP) synchronically with the acquisition of electrocardiography (ECG) and blood pulse signals. ODP was assessed from the acquired signals that were numerically processed in a custom written program. ODP incidence was about 78%, 66%, 66% and 84% for CG, GODA, POAG, and PACG group, respectively. With advancing age, the ODP incidence increased for all subjects (Δ = 12%), the highest being for the PACG and POAG groups (Δ = 30%). GODA group did not show an age-related increase in the incidence of ODP. The ocular dicrotism, measured with non-contact ultrasonic method, was found to be a common phenomenon in elderly subjects. The increased ODP incidence in PACG and POAG group may correspond to either higher stiffness of glaucoma eyes, biochemical abnormalities in eye tissues, changes in ocular hemodynamics, may reflect the effect of medications or be a combination of all those factors. The results of GODA group suggest different mechanisms governing their ocular pulse that makes them less susceptible to generating ODP and having decreased predisposition to glaucoma.